Kinetics and Mechanism of Oxidation ofPhenols by Pyridinium Dichromate - Palaniappan, A.N.; Ravishankar, M.; Sekar, K.G. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of phenols by pyridinium dichromate (PDC) has been studied in 60% acetic acid-water (v/v) medium. The reaction shows unit order dependence each with respect to oxidant and substrate. The reaction is acid catalysed and the medium of low dielectric constant favours the reaction. Increase in ionic strength has no effect on the reaction rate. In the case of substituted phenols, the order with respect to substrate varies depending upon the nature of the substituent present in the ring. In general, the electron withdrawing substituents retard the reaction rate while the electron releasing substituents enhance the rate of the reaction. From the kinetic data obtained the activation parameters have been computed and a suitable mechanism has been proposed in accordance with muliparameter correlation analysis.